convert each complex number to polar form. \( \begin{array}{ll}4.9+2 i & \text { 5. }-7 \\ 6.9 i & \text { 7. }-3-3 i \\ 8 .-5+7 i & \text { 9. } \frac{\sqrt{3}}{4}-\frac{1}{4} i\end{array} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To convert the given complex numbers to polar form, we will use the formula: \[ r = \sqrt{x^2 + y^2} \] \[ \theta = \tan^{-1}\left(\frac{y}{x}\right) \] Here, \( r \) represents the magnitude and \( \theta \) the argument (angle) of the complex number \( z = x + yi \). 1. **For \( 4.9 + 2i \)**: - \( r = \sqrt{(4.9)^2 + (2)^2} = \sqrt{24.01 + 4} = \sqrt{28.01} \approx 5.29 \) - \( \theta = \tan^{-1}\left(\frac{2}{4.9}\right) \approx 0.3805 \, \text{radians} \) - Polar Form: \( 5.29\left(\cos(0.3805) + i\sin(0.3805)\right) \) 2. **For \( -7 \)**: - \( r = 7 \) - \( \theta = \tan^{-1}\left(\frac{0}{-7}\right) = \pi \) (since it's on the negative x-axis) - Polar Form: \( 7(\cos(\pi) + i\sin(\pi)) \) 3. **For \( 6.9i \)**: - \( r = 6.9 \) - \( \theta = \frac{\pi}{2} \) (since it's on the positive imaginary axis) - Polar Form: \( 6.9(\cos(\frac{\pi}{2}) + i\sin(\frac{\pi}{2})) \) 4. **For \( -3 - 3i \)**: - \( r = \sqrt{(-3)^2 + (-3)^2} = \sqrt{9 + 9} = \sqrt{18} = 3\sqrt{2} \) - \( \theta = \tan^{-1}\left(\frac{-3}{-3}\right) = \frac{5\pi}{4} \) (in the third quadrant) - Polar Form: \( 3\sqrt{2}\left(\cos\left(\frac{5\pi}{4}\right) + i\sin\left(\frac{5\pi}{4}\right)\right) \) 5. **For \( 8 - 5 + 7i \)** (interpreted as \( 8 - 5 + 7i \)): - First combine the real parts if needed. - Let's assume you meant: \( (8 - 5) + 7i = 3 + 7i \) - \( r = \sqrt{(3)^2 + (7)^2} = \sqrt{9 + 49} = \sqrt{58} \) - \( \theta = \tan^{-1}\left(\frac{7}{3}\right) \approx 1.1659 \) - Polar Form: \( \sqrt{58}\left(\cos(1.1659) + i\sin(1.1659)\right) \) 6. **For \( \frac{\sqrt{3}}{4} - \frac{1}{4}i \)**: - \( r = \sqrt{\left(\frac{\sqrt{3}}{4}\right)^2 + \left(-\frac{1}{4}\right)^2} = \sqrt{\frac{3}{16} + \frac{1}{16}} = \sqrt{\frac{4}{16}} = \frac{1}{2} \) - \( \theta = \tan^{-1}\left(\frac{-\frac{1}{4}}{\frac{\sqrt{3}}{4}}\right) = \tan^{-1}\left(-\frac{1}{\sqrt{3}}\right) = -\frac{\pi}{6} \) - Polar Form: \( \frac{1}{2}\left(\cos\left(-\frac{\pi}{6}\right) + i\sin\left(-\frac{\pi}{6}\right)\right) \) In summary, the polar forms are: 1. \( 5.29\left(\cos(0.3805) + i\sin(0.3805)\right) \) 2. \( 7(\cos(\pi) + i\sin(\pi)) \) 3. \( 6.9\left(\cos\left(\frac{\pi}{2}\right) + i\sin\left(\frac{\pi}{